THE IMPORTANCE OF SENSORY EDUCATION IN DEVELOPING THE IMAGINATION OF VISUALLY IMPAIRED CHILDREN - Saodat MINGNOROVA; Lobar MUKHTAROVA (Scholar Express Journal, 2023)
In this article, the methods of forming the imagination of children with visual impairments, the importance of sensory education are discussed with pedagogical and psychological evidence.
Keywords: blind student; sensory education; special pedagogy; thinking